2021
DOI: 10.1002/mds.28839
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Dynamics of Large‐Scale Cognitive Networks in Huntington's Disease

Abstract: A BS TRACT: Background: Huntington's disease is a neurodegenerative disorder characterized by clinical alterations in the motor, behavioral, and cognitive domains. However, the structure and disruptions to large-scale brain cognitive networks have not yet been established. Objective: We aimed to profile changes in large-scale cognitive networks in premanifest and symptomatic patients with Huntington's disease. Methods: We prospectively recruited premanifest and symptomatic Huntington's disease mutation carrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…Dyn-ICA can examine time-varying and dynamic extensions of component analysis, which can be accomplished by using a classic component analysis within a sliding window setting ( 55 ), and isolate the signal from the noise and boost the sensitivity to identify individual differences ( 56 ). Previous studies have used Dyn-ICA to observe the pathological characteristics of diseases ( 43 ), and we are the first to use Dyn-ICA to study the mechanism of the effect of acupuncture. Similarly, our studies have clearly shown that Dyn-ICA increases sensitivity to variations between individuals or conditions ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dyn-ICA can examine time-varying and dynamic extensions of component analysis, which can be accomplished by using a classic component analysis within a sliding window setting ( 55 ), and isolate the signal from the noise and boost the sensitivity to identify individual differences ( 56 ). Previous studies have used Dyn-ICA to observe the pathological characteristics of diseases ( 43 ), and we are the first to use Dyn-ICA to study the mechanism of the effect of acupuncture. Similarly, our studies have clearly shown that Dyn-ICA increases sensitivity to variations between individuals or conditions ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Seeds used to build the matrices were obtained from our previous multi-voxel pattern analysis results ( 23 ) ( Supplementary Figure 1 ) and static ICA results in this study ( Figure 3A ). Then, the aggregated data were divided into 12 circuits using Dyn-ICA with 30 smoothing kernels, in line with a previous study's method ( 43 ). This processing produces multiple outputs, including the individual subject-level matrices gamma and the variability and frequency of the dynamic circuit time series.…”
Section: Methodsmentioning
confidence: 99%
“…( Wolf et al, 2015 ) The caudate nucleus was most frequently implicated (n = 5), showing both increased and decreased connectivity. ( Aracil-Bolaños et al, 2022 , Muller et al, 2016 , Wolf et al, 2014 , Werner et al, 2014 , Quarantelli et al, 2013 ) Among other regions, the superior frontal, parietal, and inferior temporal cortex similarly showed both increased and decreased connectivity ( Fig. 1 , Fig.…”
Section: Resultsmentioning
confidence: 92%
“…For chorea, 12 articles were included, ( Sanchez-Castaneda et al, 2017 , Sarappa et al, 2017 , Dumas et al, 2013 , Aracil-Bolaños et al, 2022 , Gargouri et al, 2016 , Liu et al, 2016 , Muller et al, 2016 , Wolf et al, 2015 , Wolf et al, 2014 , Werner et al, 2014 , Quarantelli et al, 2013 , Poudel et al, 2014 ) all concerning Huntington’s disease (HD) and well-matched for age and gender. The number of patients per study varied from 10 to 43.…”
Section: Resultsmentioning
confidence: 99%
“…A recent EEG-fMRI study of neurotypical controls resting with eyes open found that lower aperiodic activity correlated with higher hemodynamic activity in prefrontal regions (Jacob, Roach, Sargent, Mathalon, & Ford, 2021). It may be that lower aperiodic activity in the HD group during the eyes open condition reflected greater activation of prefrontal cognitive control networks to sustain attentional control and compensate for the impact of HD pathology on frontostriatal networks (Aracil-Bolanos et al, 2022; Jacob et al, 2021; Pini et al, 2020). These group differences may also only have emerged in the eyes open condition due to the increased need for cognitive control precipitated by the external demands on attention that accompany eyes open paradigms (Barry & De Blasio, 2017; Boytsova & Danko, 2010).…”
Section: Discussionmentioning
confidence: 99%